Conversion of pyrolytic non-condensable gases from polypropylene co-polymer into bamboo-type carbon nanotubes and high-quality oil using biochar as catalyst. (1st January 2022) - Shah, Kalpit; Patel, Savankumar; Halder, Pobitra; Kundu, Sazal; Marzbali, Mojtaba Hedayati; Hakeem, Ibrahim Gbolahan; Pramanik, Biplob Kumar; Chiang, Ken; Patel, Tejas
Abstract: The conversion of low-value plastic waste into high-value products such as carbon nanomaterial is of recent interest. In the current study, the non-condensable pyrolysis gases, produced from Polypropylene Copolymer (PPC) feedstock, was converted into bamboo-type carbon nanotubes (BCNTs) through catalytic chemical vapour deposition using biochar. Experiments were conducted in a three-zone furnace fixed bed reactor, where PPC was pyrolysed in the second zone and carbon nanotubes (CNTs) growth was eventuated in the third zone. The effects of different growth temperatures (500, 700, 900 °C) and biochar particle sizes (nanoparticle as well as 0–100 and 100–300 μm) were investigated to optimise the production of hydrogen and the yield of carbon nanotubes on the biochar surface. Biochar samples used in the synthesis of CNTs were obtained from the pyrolysis of saw dust at 700 °C in a muffle furnace. Analyses performed by using Scanning electron microscopy, Transmission electron microscopy, X-ray diffraction, and Raman spectroscopy techniques suggested that the best crystalline structure of CNTs were obtained at 900 °C with nano-sized biochar as a catalyst. The strong gas-solid contact and void fraction of nano-sized particles enhances the diffusion–precipitation mechanism, leading to the growth of CNTs. The nano-sized biochar increased hydrogen production at 900 °C and reduced the polycyclic aromatic hydrocarbons content in oil to only 1%, which is advantageous for further utilisation. Therefore, the production of high-value CNTs from waste plastic using low-cost biochar catalyst can be a sustainable approach in the management of waste plastic while participating in the circular economy. Graphical abstract: Image 1 Highlights: Carbon nanotubes were produced from waste plastic using low-cost biomass-derived biochar. Carbon deposition at 900 °C for biochar nanoparticles was 15.6 times higher than 500 °C. Carbon deposition increased by ∼66% for nanoparticle biochar compared to 100–300 μm at 900 °C. Biochar nanoparticles significantly reduced polycyclic aromatic hydrocarbons in oil. Synthesis of carbon nanotubes from waste plastic can be a sustainable route of circular economy.